2005
DOI: 10.1097/01.aog.0000178754.88912.b9
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Levonorgestrel-Releasing Intrauterine System and Breast Cancer

Abstract: The results suggest that the use of the levonorgestrel-releasing intrauterine system is not associated with an increased risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(60 citation statements)
references
References 15 publications
3
45
0
12
Order By: Relevance
“…46,47 In addition, when used by premenopausal women after initiation of breast cancer treatment, the LNG-IUD does not appear to increase the risk of breast cancer recurrence. 48 Thus, for premenopausal women who wish to retain fertility but have menstrual disturbances, the LNG-IUD seems to be a reasonable, short-term treatment.…”
Section: Aub Caused By Anatomic Abnormalitiesmentioning
confidence: 99%
“…46,47 In addition, when used by premenopausal women after initiation of breast cancer treatment, the LNG-IUD does not appear to increase the risk of breast cancer recurrence. 48 Thus, for premenopausal women who wish to retain fertility but have menstrual disturbances, the LNG-IUD seems to be a reasonable, short-term treatment.…”
Section: Aub Caused By Anatomic Abnormalitiesmentioning
confidence: 99%
“…On the other hand, no increase in BC risk was found in a population-based case-control study [14]. The role of hormone-releasing intrauterine device (HR IUD) in the etiology of BC has also been under discussion, and the results are somewhat contradicting [15][16][17][18]. With respect to use of hormone replacement therapy (HRT), several studies have indicated that HRT use increases the risk of BC.…”
Section: Introductionmentioning
confidence: 99%
“…The Backman study included LNG-IUS users of all ages with the dominant group being 35-39 years old. There was no significant difference in BC incidence between LNG-IUS users and the general female population in any of the evaluated age groups; however, in the 35-39 age group (i.e., women reaching late 30's/approximating early 40's), the incidence was higher in LNG-IUS users and the differences trended towards significance (p = 0.056) [9]. In the Soini study (women aged 30-49 years with an average follow-up of [10 years), LNG-IUS users had an increased risk for ductal breast cancer (standardized incidence ratio [SIR] 1.20) and lobular breast cancer (SIR 1.33; latter mostly luminal subtypes) [11].…”
Section: Discussionmentioning
confidence: 74%
“…Of the four studies investigating the association between LNG-IUS use and BC, our study design is more similar to the studies reported by Backman et al and Soini et al [9,11,12]. In these studies involving 17,360 LNG-IUS users (all indications) and 93,843 LNG-IUS users (for treating/preventing menorrhagia), respectively, BC incidence was compared between LNG-IUS users and the general female population.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation